Richard Swinburne : Christian Philosophy in a Modern World. - Mößner, Nicola (Münstersche Vorlesungen zur Philosophie (Series), 2008)
Richard Swinburne is one of the most influential contemporary proponents of the analytical philosophy of religion. He is, above all, a traditional theist, i.e. he believes, that there exists an eternal, uncreated and immaterial perfect soul called "God" which is omnipotent, omniscient, perfectly free, morally perfect and the creator and sustainer of the universe. However, his interests are very wide-ranging. He has written on almost every central theological and philosophical issue such as epistemology, metaphysics, theory of mind and ethics. Swinburne is particularly well-known for his percep.